A h-Adaptive Algorithm Using Residual Error Estimates for Fluid Flows (Communications in Computational Physics, 2018)
Algorithms for adaptive mesh refinement using a residual error estimatorare proposed for fluid flow problems in a finite volume framework. The residual errorestimator, referred to as the ℜ-parameter is used to derive refinement and coarseningcriteria for the adaptive algorithms. An adaptive strategy based on the ℜ-parameteris proposed for continuous flows, while a hybrid adaptive algorithm employing acombination of error indicators and the ℜ-parameter is developed for discontinuousflows. Numerical experiments for inviscid and viscous flows on different grid topologies demonstrate the effectiveness of the proposed algorithms on arbitrary polygonalgrids.